2022
DOI: 10.3390/polym14112253
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Polypropylene with Additives of Bi2O3 Nanoparticles as Radiation-Shielding Materials

Abstract: This work aimed to intensively study polypropylene samples (PP) embedded with micro- and nanoparticles of Bi2O3 for their application in radiation shielding. Samples were prepared by adding 10%, 20%, 30%, 40%, and 50% of Bi2O3 microparticles (mBi2O3) by weight, and adding 10% and 50% of Bi2O3 nanoparticles (nBi2O3), in addition to the control sample (pure polypropylene). The morphology of the prepared samples was tested, and also, the shielding efficiency of gamma rays was tested for different sources with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The results showed that adding nanoparticles to HSC enhanced its radiation shielding properties, with applications in both civil engineering structures and the potential to be used as a building material for nuclear plants. Additionally, the results of many studies showed that adding different percentages of nanoparticles may eliminate the porosity in concrete, in addition to binding cement particles to each other, which enhances the structure and efficiency of concrete due to its small size, which is usually less than 100 nanometers [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that adding nanoparticles to HSC enhanced its radiation shielding properties, with applications in both civil engineering structures and the potential to be used as a building material for nuclear plants. Additionally, the results of many studies showed that adding different percentages of nanoparticles may eliminate the porosity in concrete, in addition to binding cement particles to each other, which enhances the structure and efficiency of concrete due to its small size, which is usually less than 100 nanometers [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 d shows the results of changing the value of Z eff depending on the energy of shielded gamma rays, calculated according to the methodology proposed in [ 27 , 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that in recent years, the research and development of various combinations of glass, polymer, and nanoparticle compositions for radiation protection has become a highly topical, and as a result, many different glass combinations have been successfully synthesized and evaluated [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Iron (Fe 3+ ) stearate (FeSt 3 ) can chemically promote fracture points of polymer carbon chains under heating via thermo-oxidation processes, which helps to break down polymer macromolecules and speeds up the degradation processes partially. [13][14][15][16] Iron (Fe 3+ ) ions, under the effects of heat and/or sunlight, can decompose the hydroperoxides (RCOO) formed during the polymer degradation, leading to chain scission of polymers without the need for metal catalysts (Scheme 1a). [17][18][19] In addition, the polymer's chain disassembly due to chain scissions results in scattering oligomer fragments with hydroxyl and carbonyl functional groups, increasing the hydrophilicity of the polymer surfaces and promoting their interactions with microorganisms to enhance the biodegradation process.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 El-Khatib et al reported that the filler structure of Bi 2 O 3 particles could improve the morphological and mechanical properties of polypropylene (PP) films by reducing the voids in the polymers. 15 Additionally, the high reactivity of Bi 2 O 3 with released carbon dioxide (CO 2 ) to produce bismuth carbonate could reduce the amount of carbon emission from biodegradation processes which add up to its competitiveness. 22 In this research, the impacts of both FeSt 3 and Bi 2 O 3 as additives on the biodegradation properties of various renewable polymers [poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(butylene adipate-co-terephthalate) (PBAT), cellulose acetate (CA), poly(lactic acid) (PLA), and thermoplastic starch (TPS)] were investigated under aerobic degradation and soil burial environments.…”
Section: Introductionmentioning
confidence: 99%